Aryl hydrocarbon receptor activation and CYP1A induction by cooked food-derived carcinogenic heterocyclic amines in human HepG2 cell lines. (November 2016) - Sekimoto, Masashi; Sumi, Haruna; Hosaka, Takuomi; Umemura, Takashi; Nishikawa, Akiyoshi; Degawa, Masakuni
Abstract: The ability of nine cooked food-derived heterocyclic aromatic amines (HCAs), such as 3-amino-1, 4-dimethyl-5 H -pyrido[4, 3- b ]indole (Trp-P-1), 3-amino-1-methyl-5 H -pyrido[4, 3- b ]indole (Trp-P-2), 2-amino-6-methylpyrido[12- a :3′, 2′- d ]imidazole (Glu-P-1), 2-amino-pyrido[12- a :3′, 2′- d ]imidazole hydrochloride (Glu-P-2), 2-amino-9 H -pyrido[2, 3- b ]indole (AαC), 2-amino-3-methyl-9 H -pyrido[2, 3- b ]indole (MeAαC), 2-amino-3-methylimidazo[4, 5- f ]quinolone (IQ), 2-amino-3, 8-dimethylimidazo[4, 5- f ]quinoxaline (MeIQx) and 2-amino-1-methyl-6-phenyl-1 H -imidazo[4, 5- b ]pyridine (PhIP), to activate human aryl hydrocarbon receptor (hAhR) was examined using a HepG2-A10 cell line, which has previously established from human hepatocarcinoma-derived HepG2 cells for use in hAhR-based luciferase reporter gene assays. Trp-P-1, Trp-P-2, AαC, MeAαC, IQ and MeIQx showed a definite ability to induce not only luciferase (hAhR activation) in HepG2-A10 cells but also cytochrome P450 (CYP)1A1/1A2 mRNAs in HepG2 cells, while such the ability of Glu-P-1, Glu-P-2, and PhIP was very low. In addition, all the HCAs examined, especially MeAαC and MeIQx, had a definite capacity for inhibiting the activity of ethoxyresorfin O -deethylase (CYP1As, especially CYP1A1). The present findings demonstrate that all the HCAs examined have the ability to activate hAhR and its target genes, and further confirm that these HCAs become good substrates for human CYP1A subfamily enzyme(s). Graphical abstract: Highlights: All the food-derived carcinogenic heterocyclic amines (HCAs) used have the ability to induce CYP1A subfamily enzyme(s) in a hAhR-dependent fashion. All the HCAs used, especially MeAαC, become good substrates for human CYP1A subfamily enzyme(s) and show inhibitory effects on the activity of ethoxyresorufin O -deethylase (mainly CYP1A1). MeAαC has the ability to inhibit the activity of ethoxyresorufin O -deethylase than alpha-naphthoflavone, a representative CYP1A enzyme(s).